2013
DOI: 10.5604/17322693.1061412
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesiology and the cytokine network

Abstract: The immune response is a highly specific reaction carried out by means of specialized cells that belong to the immune system. There are two types of immune response mechanisms aimed towards pathogens: non-specific, innate reactions, and specific, acquired reactions. Acquired immunity, characterized by its specificity, is comprised of lymphocytes, including both T cell and B cell populations. The role of B lymphocytes is not limited to the humoral response, though the cellular immune response is carried out mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 0 publications
1
27
0
1
Order By: Relevance
“…Meanwhile, this study also found that the level of serum IL-10 ascended almost synchronously with IL-8 level and there was positive association, suggesting that cytokine secretion in vivo was similar to network, marked by compensatory increase of IL-10 secretion due to the ascending IL-8 level so as to maintain the balance of pro-and anti-inflammatory cytokines, which was consistent with relevant report (Lisowska et al, 2013). Though the influence of propofol on cytokines proved in this study, no unfavorable prognosis (sepsis and multiple organ failure) was observed in all patients in the following clinical observation, indicating that the selection of anesthetic agents that influenced the balance of cytokines had played no effect on immune homeostasis of human body.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, this study also found that the level of serum IL-10 ascended almost synchronously with IL-8 level and there was positive association, suggesting that cytokine secretion in vivo was similar to network, marked by compensatory increase of IL-10 secretion due to the ascending IL-8 level so as to maintain the balance of pro-and anti-inflammatory cytokines, which was consistent with relevant report (Lisowska et al, 2013). Though the influence of propofol on cytokines proved in this study, no unfavorable prognosis (sepsis and multiple organ failure) was observed in all patients in the following clinical observation, indicating that the selection of anesthetic agents that influenced the balance of cytokines had played no effect on immune homeostasis of human body.…”
Section: Discussionsupporting
confidence: 91%
“…The influences of different anesthetic agents on serum cytokine expressions of surgical patients have become a hot-topic in recent researches (Schilling et al, 2011;Lisowska et al, 2013). Multiple studies found that anesthetic agents had significant influence on serum cytokines in patients who underwent surgeries (Dermitzaki et al, 2009;Reikerås et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several results have confirmed the relationship between operative technique and cytokine response. They underline the importance of cytokine network changes that can play a role in the quality of post-operative care [7]. IFN-γ and IL-4 are the main cytokines that regulate the switch of immune response either toward cell-mediated (pro-inflammatory) Th-1 type or humoral (anti-inflammatory) Th-2 type.…”
Section: Resultsmentioning
confidence: 99%
“…Anaesthetic drugs generally induce an increase in leucocytes counts 9,[13][14][15][16][17] exerting diverse effects on each of different immune cell subpopulation (Table 2). In the next section, most Propofol ↓ phagocytosis and respiratory burst and ↑ cell counts 13,14,16,18 Isoflurane ↓ phagocytosis and respiratory burst 16,18 Bupivacaine ↓ phagocytosis and chemotaxis 16,18 Lidocaine ↓ phagocytosis and chemotaxis 16,18 Desflurane ↑ cell counts Midazolam ↓ phagocytosis and respiratory burst 15,18 Thiopental ↓ phagocytosis and respiratory burst 15,18 Lidocaine ↓ cell counts Sevoflurane ↓ cell counts 14,21 Halothane ↓ cell counts 14,21 Isoflurane ↑ cell counts 13,25 Desflurane ↑ cell counts 13,25 Isoflurane ↑ apoptosis…”
Section: Effects Of Anaesthetic Drugs On Immune Cellsmentioning
confidence: 99%
“…. Intravenous anaesthetics, such as propofol, midazolam and thiopental, inhibit both phagocytosis and respiratory burst 15,18 . Halothane and lidocaine decrease mononuclear cell counts by enhancing their apoptosis 10 .…”
Section: Introductionmentioning
confidence: 99%